UPAYA MENINGKATKAN HASIL BELAJAR IPS DENGAN MENERAPKAN METODE TIME TOKEN ARENDS PADA SISWA KELAS VII SMP NEGERI 1 GAUNG - Susi Kurniati (Jurusan Pendidikan Ilmu Pengetahuan Sosial Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2020)
This study aims to improve the social studies learning outcomes of Grade VII students of SMP Negeri 1 Gaung by applying the Time Token Arends method. This research is a Classroom Action Research conducted in 3 (three) cycles with stages of planning, implementation and observation, and reflection. Where each cycle consists of 1 (one) meeting. The conclusion of this study is that the Time Token Arends method has a positive impact in improving student learning outcomes which is characterized by an increase in student learning completeness in each cycle, namely cycle I (27.59%), cycle II (51.72%) and cycle III (89.66%).